2022
DOI: 10.3390/antiox11030524
|View full text |Cite
|
Sign up to set email alerts
|

HDL Accessory Proteins in Parkinson’s Disease—Focusing on Clusterin (Apolipoprotein J) in Regard to Its Involvement in Pathology and Diagnostics—A Review

Abstract: Parkinson’s disease (PD)—a neurodegenerative disorder (NDD) characterized by progressive destruction of dopaminergic neurons within the substantia nigra of the brain—is associated with the formation of Lewy bodies containing mainly α-synuclein. HDL-related proteins such as paraoxonase 1 and apolipoproteins A1, E, D, and J are implicated in NDDs, including PD. Apolipoprotein J (ApoJ, clusterin) is a ubiquitous, multifunctional protein; besides its engagement in lipid transport, it modulates a variety of other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 187 publications
(301 reference statements)
0
9
0
Order By: Relevance
“…As a scavenger, it combines misfolded toxic proteins or plasmin-generated protein fragments (PGPFs) to form complexes, which are recognized by membrane receptors and transported in cells, where they are degraded by proteasomes or lysosomes. As for chelating ability, it acts as a chelating agent around misfolded toxic molecules in excess protein molecules to prevent their toxicity ( Berdowska et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a scavenger, it combines misfolded toxic proteins or plasmin-generated protein fragments (PGPFs) to form complexes, which are recognized by membrane receptors and transported in cells, where they are degraded by proteasomes or lysosomes. As for chelating ability, it acts as a chelating agent around misfolded toxic molecules in excess protein molecules to prevent their toxicity ( Berdowska et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…37,38 The dysregulation of LCAT leads to the disturbance of lipid metabolism and it is potentially implicated in the pathogenesis of PD. 39 Recent plasma metabolomics analyses underscore this by revealing a decrease in lipid and lipid-associated molecules in PD compared to the control group. 40 Our findings showed that LCAT was downregulated in PSP patients compared to PD and HC, suggesting the link between lipid metabolism disturbance by LCAT dysregulation and PSP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results show that most of these proteins have several reported interactors and thus may be involved in the formation of large complexes. An illustration of this phenomenon is found in the protein clusterin (CLU gene), also known as apolipoprotein J, which has been implicated in the metabolism of aggregation-prone proteins, including those associated with NDs [31][32][33]. Notably, clusterin's interaction with Aβ42 has been demonstrated to enhance its clearance from the brain through the blood-brain barrier (BBB) [31].…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the functional enrichment analysis of the altered proteins discovered in both strategies that highlight the involvement of those proteins in lipoprotein metabolism and HDL-mediated lipid transport pathways. Cumulatively, all these findings point to the relevance of lipoproteins in the context of NDs and, although not absolutely clear, the link between these diseases, in particularly AD, and apolipoproteins has been the focus of many studies [31,33,[36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation